A New Method of Secure Communication with Crystography - Suganya. A; Sharmila. R; Gopinathan. N (International Journal of Computer Sciences and Engineering, 2014)
In the development of digital communication the need for security of data is often required. In this paper, a new method is Crystography, a combination of Cryptography and Steganography together through image processing. Cryptography is the process of converting the data into gibberish form whereas; Steganography is to embed secret data in a multimedia file as carriers, so that it will not be able to detect that a secret data existing in the file. This system is able to perform both techniques using keys for Cryptography and image as cover objects for Steganography. So, first the data is converted into cipher text using RSA algorithm of Cryptography. Secondly the encrypted data is to be hidden using LSB algorithm of Steganography. By combining both techniques more security is obtained.